The relationship between Modic changes and intervertebral disc degeneration - Määttä, Juhani H. (BMC Musculoskelet Disord, 2016)
BACKGROUND: Recent reported results have added to the weight of evidence supporting association between disc degeneration and Modic changes. Endplate or Modic changes are also associated with increased body mass index. The most recent study from Teichtahl et al. titled ‘Modic changes in the lumbar spine and their association with body composition, fat distribution and intervertebral disc height – a 3.0 T-MRI study’ showed associations of Modic changes with quantitatively measured reduced disc height and fat mass index. However, there were some facts, which we would like to address in this Correspondence to their article. DISCUSSION: The different components of intervertebral disc degeneration such as loss of disc height and disc signal intensity have already been shown associated with endplate changes – but not disc height if it is assessed using newer more precise methods of quantitation of disc height. A possible protective effect of different adiposity distribution in the body to Modic change development would be of interest if observed in a longitudinal study in the future. SUMMARY: Modic changes have been associated with different components of intervertebral disc degeneration such as loss of disc height and disc signal intensity previously. The influence of body fat distribution on endplate changes would be interesting to study longitudinally.